2008
DOI: 10.4161/psb.6789
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the network

Abstract: The arbuscular mycorrhhiza (AM) symbiosis involves an intricate network of signaling and biochemical pathways designed to ensure that a beneficial relationship is established between the plant and fungal partners as a result of a mutual nutrient exchange. Emerging data has been recently published to explain why the relationship is not always fair, as observed in prevalent parasitic AM relationships in which the plant host receives no phosphorus (P) in exchange for carbon (C) delivered to the fungus. The theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 142 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…Although nutrient limitation might be a possible explanation because fungal hyphae have large N requirements (Hodge & Fitter, 2010), the concentration of NO 3 − and P in inoculated soils remained high, suggesting that C-limitation was a more likely explanation. The establishment of the symbiotic relation between AM fungus and plant requires an expenditure of C from the plant (Délano-Frier & Tejeda-Sartorius, 2008), potentially limiting C availability to microbes in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Although nutrient limitation might be a possible explanation because fungal hyphae have large N requirements (Hodge & Fitter, 2010), the concentration of NO 3 − and P in inoculated soils remained high, suggesting that C-limitation was a more likely explanation. The establishment of the symbiotic relation between AM fungus and plant requires an expenditure of C from the plant (Délano-Frier & Tejeda-Sartorius, 2008), potentially limiting C availability to microbes in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Under the HM stress condition, AMF also regulate the balance of the phytohormones by intervening in the communication of signals during the process of AMF-plant symbiotic association (Smith and Read, 2008;Li et al, 2018). Phytohormones, as a kind of endogenous plant signal, are the most sensitive responders in these processes, and they stimulate plants to show appropriate responses to adapting to HM stress (Ludwig-Müller, 2000;Délano-Frier and Tejeda-sartorius, 2008). Therefore, AMF contribute to building a productive, healthy, and sustainable ecosystem, with vegetation recovery in HM-contaminated areas.…”
Section: Introductionmentioning
confidence: 99%
“…symbiotic system) was determined not only in arbuscules but also in the intercellular hyphae, which indicated that both structures appear to be important for sugar unloading [44]. The mycelium of the AM fungi probably receives carbohydrates from the apoplast of the root cortex [5] as glucose [46], and less as sucrose [2]. The exact location and mechanism of carbon transfer from host plants to AM fungi is not yet fully discovered, but it is the focus of recent studies of plant-microbial symbiotic interactions [17,18,[27][28][29]33].…”
Section: Discussionmentioning
confidence: 99%
“…Plant carbohydrate metabolism was shown to change significantly during AM formation. The host plant transfers up to 30% of assimilates towards the AM fungus [2,25]. Besides carbohydrates, it donates other metabolites, such as fatty acids, known to be used as a source of organic carbon directed in the synthesis of fungal lipids [26].…”
Section: Carbohydrate Metabolism Of Am Plantsmentioning
confidence: 99%
See 1 more Smart Citation